CORPORATE SOCIAL RESPONSIBILITY TERHADAP MANAJEMEN LABA DAN KINERJA PERUSAHAAN - Devi Dwi Rahmawardani; Muslichah Muslichah (JRAK, 2020)
This study aims to analyze the direct and indirect effects of Corporate Social Responsibility (CSR) on company performance through earnings management. The objects in this study are companies incorporated in LQ45 in the 2016-2018 period. Samples were taken using a purposive sampling method. The data of this study were analyzed using path analysis. The results showed four important findings: (1) the influence of CSR on company performance is positive and significant, (2) CSR has a negative and significant effect on earnings management, (3) the effect of earnings management on company performance is not significant (4) earnings management cannot mediate the effect of CSR on company performance.